Apollodoros the son of Pasion - Trevett, J; Trevett, J. C. (1990)
﻿ This thesis is a study of the fourth century B.C. Athenian politician Apollodoros the son of Pasion of Acharnae, and of the speeches which he delivered and which are preserved in the Corpus Demosthenicum. Chapter 1 contains a chronological survey of the lives of Pasion and Apollodoros. In Chapter 2, which contains an examination of the financial circumstances of the family, I am concerned not merely to tackle the vexed question of the size of Pasion's estate, but also to analyse the sources of that wealth, and the uses to which it was put. In Chapter 3 I examine the question of the authorship of the speeches which Apollodoros delivered, including the performance of some simple stylistic tests, which reveal a clear difference of style between these speeches and the genuine private speeches of Demosthenes. In Chapter 4 I discuss the form and function of the speeches, examining how far they diverge from the practice of other Athenian orators, and how far they are influenced by rhetorical theory. I also seek to question the generally held view that they are incompetently composed, and suggest that any diverges from Demosthenic practice or from rhetorical theory should not necessarily be considered indicative of a lack of ability on the part of their author. In Chapter 5 I try to assess whether Apollodoros received a rhetorical education, and I examine the likely sources of his legal and historical knowledge. In Chapter 6 I examine in detail one particular aspect of the speeches: the inclusion of a long and detailed historical narrative in Against Neaera. I attempt to determine the sources of this account, and then to look for any signs elsewhere in the speeches of an historical interest on Apollodoros' part. Chapter 7 deals with Apollodoros' political career, whilst in Chapter 8 I examine the position of the family within Athenian society. I attempt to determine the social circles in which Pasion and Apollodoros moved, the extent to which they were accepted into Athenian high society, and the ways in which they tried to use their money to acquire social acceptance. The two appendices contain a discussion of the authenticity of documents preserved in the manuscripts of the speeches, and the data from two stylistic tests which I performed.